Effect of storage on physical, chemical, microbial and sensory qualities of instant masa flour produced from blends of rice and Bambara groundnut - Balogun, Mutiat A; Oyeyinka, Samson A; Kolawole, Fausat L; Dauda, Adegbola O; Abdulmalik, Aisha J (Journal of Agricultural Sciences (Belgrade), 2021)
Masa is a traditionally fermented meal usually made from cereals. The aim of this research was to produce an enriched meal from rice and Bambara groundnut. The colour, functional properties and microbial quality of composite blend of rice and Bambara groundnut flour, in the ratio 100:0, 95:5, 90:10, 85:15, 80:20 were evaluated using standard methods. Sensory properties of freshly made masa and masa prepared from stored flours were also determined. The microbial load of the masa flour blend increased over the storage period. Water absorption capacity, swelling capacity and bulk densities increased, while the oil absorption capacity decreased with increase in storage period. Objective colour result showed decrease in the lightness (L*) value. Sensory properties of masa were not substantially altered with Bambara groundnut inclusion, but the ratings reduced with storage. Instant masa may be prepared from flour stored for 4 weeks, without considerable changes in quality.